Increased adrenomedullin immunoreactivity and mRNA expression in coronary plaques obtained from patients with unstable angina. Issue 10 (14th September 2004) - Ishikawa, T; Hatakeyama, K; Imamura, T; Ito, K; Hara, S; Date, H; Shibata, Y; Hikichi, Y; Asada, Y; Eto, T
Abstract : Objective: To examine the expression and localisation of adrenomedullin in human coronary atherosclerotic lesions from patients with unstable angina (UAP) and stable angina (SAP), and to study the relation between adrenomedullin expression and plaque instability. Design: A retrospective observational study. Patients: Directional coronary atherectomy samples were obtained from 15 patients with UAP and 12 with SAP. Methods: The localisation of adrenomedullin was examined by immunohistochemistry, and adreno-medullin mRNA expression was measured by quantitative polymerase chain reaction. Results: Adrenomedullin immunoreactivity was preferentially localised in macrophages, intimal smooth muscle cells, and proliferated microvessels. The mean number of adrenomedullin positive cells in five high power fields (× 400) per specimen was higher in patients with UAP than in those with SAP (mean (SEM), 110 (13) v 76 (7); p < 0.05); and the ratio of adrenomedullin positive to total cells was higher in patients with UAP (43.0 (2.2)% v 34.2 (2.0)%; p < 0.01). More adrenomedullin mRNA was expressed in the plaque of patients with UAP than in those with SAP (60.4 (16.9)% v 9.7 (3.3)%; p < 0.01). Conclusions: The findings suggest that adrenomedullin is involved in the development of atherosclerosis and plaque instability in human coronary arteries, in an autocrine or paracrine manner.